1999
DOI: 10.1177/00220345990780100501
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Induces Cystatin S-like Substances in Submandibular Saliva of the Rat

Abstract: Irritating dietary substances such as tannin and papain have been reported to alter the morphology of salivary glands and their secretions. Such alterations can be one line of protection from toxic or irritating substances in food. We investigated the effects of dietary capsaicin (a pungent ingredient of hot red pepper) on the rat submandibular gland and its secretions. Several groups of animals were offered either control diets or diets containing capsaicin (from 0.0001 to 0.1%) for seven days. Higher concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…A new and very interesting finding is the presence of cystatins in the precipitated fractions after tannic acid addition to the saliva of hamadryas baboons. The induction of cystatin SA was earlier shown in rat submandibular saliva and was suggested to be one line of protection of oral mucosa from toxic or irritating phytochemicals, such as capsaicin [Katsukawa & Ninomiya, 1999; Katsukawa et al, 2002]. However, our study is the first to demonstrate an interaction of cystatin SA with tannins in a primate species.…”
Section: Discussionsupporting
confidence: 58%
“…A new and very interesting finding is the presence of cystatins in the precipitated fractions after tannic acid addition to the saliva of hamadryas baboons. The induction of cystatin SA was earlier shown in rat submandibular saliva and was suggested to be one line of protection of oral mucosa from toxic or irritating phytochemicals, such as capsaicin [Katsukawa & Ninomiya, 1999; Katsukawa et al, 2002]. However, our study is the first to demonstrate an interaction of cystatin SA with tannins in a primate species.…”
Section: Discussionsupporting
confidence: 58%
“…Cystatin SN, a closely related protein to cystatin S, has been linked to the sensitivity to the bitter taste of caffeine in humans [23]. It has also been demonstrated that oral capsaicin [17] and quinine [18] stimulate the production of salivary cystatin S-like proteins suggesting that this class of proteins is generally responsive to aversive oral stimuli, but to our knowledge, this is the first suggestion that this protein is related to meal size.…”
Section: Discussionmentioning
confidence: 87%
“…The protein content of saliva is altered under a variety of circumstances including diet composition [13], [14], disease [15], [16], exposure to compounds like capsaicin [17] or bitter taste stimuli [18][21]. Likewise, there is evidence that some of these proteins modulate bitter taste acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Of all adverse clinical signs observed, salivation and abdominal distension probably resulted from irritation of the oral mucosa and gastrointestinal track by ZnO AE100(+) . Salivation is often observed in gavage studies and may have been a reaction to the taste or mucosal irritation of the test article [ 17 18 19 20 ]. Fur loss and weakness were indications of stress and/or malnutrition induced by ZnO AE100(+) , which is supported by the decreases in body weight and feed consumption.…”
mentioning
confidence: 99%